2013
DOI: 10.1111/jgh.12267
|View full text |Cite
|
Sign up to set email alerts
|

Continuous imaging of esophagogastric junction in patients with reflux esophagitis using 320‐row area detector CT: A feasibility study

Abstract: Continuous imaging with 320-row area detector CT is useful to evaluate morphological changes in the esophagogastric junction area in both normal individuals and patients with reflux esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…As a result, the angle of His also increases, and there is no longer a subdiaphragmatic segment of the esophagus, namely the abdominal esophagus, to be compressed. Several studies using CT or MRI showed that the angle of His was wider (more obtuse) in GERD patients than in healthy subjects [ 11 , 12 ]. In the present study, the angle of His was wider in patients with abnormal GEFV than it was in those with normal GEFV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the angle of His also increases, and there is no longer a subdiaphragmatic segment of the esophagus, namely the abdominal esophagus, to be compressed. Several studies using CT or MRI showed that the angle of His was wider (more obtuse) in GERD patients than in healthy subjects [ 11 , 12 ]. In the present study, the angle of His was wider in patients with abnormal GEFV than it was in those with normal GEFV.…”
Section: Discussionmentioning
confidence: 99%
“…The final data for each subject were obtained by calculating the mean measurement values by the two experts. The angle of His, hiatal hernia, size of the diaphragmatic hiatus, and length of the abdominal esophagus were measured using CT images using methods of previous study [ 12 ]. The techniques of the following measurements performed by gastroenterologist were verified and closely monitored by two radiologist (N.K.L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of recent advances in continuous imaging with 320 row area detector CT scan as described by Fukazawa et al [18], and positron emission tomography/computed tomography (PET/CT) as reported by Wu et al [19] for gastrointestinal disorders, these imaging modalities are not standard of care for diagnosis of GERD, so detection of ED on chest CT scan or high-resolution chest CT scan (HRCT ) is an incidental and challenging finding. Firstly, esophageal stasis may predis- …”
Section: Discussionmentioning
confidence: 99%
“…An acute esophagogastric insertion angle has been shown to be necessary to act as a flap‐valve mechanism to protect against gastroesophageal reflux, since progressive filling of the gastric fundus compresses the intra‐abdominal portion of the esophagus and reduces EGJ opening during transient LES relaxations . Widening of this angle was enlarged in patients with GERD, assessed by MRI and CT . Videofluoroscopy is often the first investigation method in patients with unspecific swallowing complaints and may show a funnel‐shaped or gaping cardia combined with widening of the angle of His and the EGJ, indicative of GERD and requiring further endoscopic and manometric workup.…”
Section: Cardiamentioning
confidence: 99%